Assessment of the Upstream Slope Stability of Darbandikhan Rockfill Dam during Drawdown - Salim, Sirwan Gh.; Noori, Krikar M. G. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Earth and rockfill dams face a variety of loading conditions during lifetime. One of the most critical loading conditions is the rapid drawdown of water level after steady state conditions. Rapid drawdown may cause instability of upstream slope of the dam. The present work examines the stability of a rockfill dam under different drawdown rates in terms of factor of safety for the upstream slope of the dam. For this purpose, a computer software named GeoStudio 2012 SEEP/W and SLOPE/W has been used for the numerical analysis. The results showed that the drawdown rate has a significant effect on stability of rockfill dam in which increasing the drawdown rate from 1 m/day to 10 m/day decreases the stability of the dam by 33%. Based on the outcomes, for the studied case the drawdown rate (1 m/day) can be recommended.